FREQUENCY OF SEROPOSITIVITY OF HELICOBACTER PYLORI IN PATIENTS PRESENTING WITH DYSPEPSIA - Naz, Farhat; Malik, Saqib; Afzal, Salim; Anwar, Syed Abbas (Journal of Ayub Medical College Abbottabad, 2013)
Background: Dyspepsia is a common health problem and most of the causes of dyspepsia are related to infection by Helicobacter pylori (H. pylori). Prevalence of H. pylori infection is different in different parts of the world. Purpose of our study was to determine the frequency of H. pylori infection in patients with dyspepsia in our setting where the prevalence of H. pylori was expected to be high. Objective of this study was to determine the frequency of H. pylori seropositivity in patients with dyspepsia. Methods: A Cross sectional, descriptive study was conducted at the Department of Medicine, Ayub Medical College, Abbottabad from March to September 2009. Patients presenting in Medical outpatient departments of Ayub Teaching Hospital, Abbottabad with dyspepsia were included in the study and interviewed according to Reflux Disease Questionnaire and their serum sent for estimation of anti H. pylori IgG antibodies by enzyme linked immunosorbent assay (ELISA). Results: A total of 92 patients were included in this study. Out of these 31 (33.7 %) were males and 61 (66.3%) were females. Out of them 68 (73.9%) were found seropositive for H. pylori by ELISA. Conclusion: H. pylori infection is frequent in patients with dyspepsia in our setting and apparently uncomplicated dyspepsia should always be tested for H. pylori and all seropositive patients should be offered eradication therapy. Keywords: Helicobacter pylori (H. pylori), dyspepsia, peptic ulcer, gastritis, non-ulcer dyspepsia